1998
DOI: 10.1103/physrevlett.81.3840
|View full text |Cite
|
Sign up to set email alerts
|

In-Loop Squeezing Is Like Real Squeezing to an In-Loop Atom

Abstract: Electro-optical feedback can produce an in-loop photocurrent with arbitrarily low noise. This is not regarded as evidence of "real" squeezing because squeezed light cannot be extracted from the loop using a linear beam splitter. Here I show that illuminating an atom (which is a nonlinear optical element) with "in-loop" squeezed light causes line narrowing of one quadrature of the atom's fluorescence. This has long been regarded as an effect that can only be produced by squeezing. Experiments on atoms using in-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…A recent letter [5] by one of us showed that squashed light also produces a similar line-narrowing, and so this "direct effect" is one of non-classical correlations rather than solely of squeezing. The work on squashed light spectroscopy of two-level atoms was recently extended to include simultaneous squeezing and squashing [3].…”
Section: Two-level Atommentioning
confidence: 99%
See 4 more Smart Citations
“…A recent letter [5] by one of us showed that squashed light also produces a similar line-narrowing, and so this "direct effect" is one of non-classical correlations rather than solely of squeezing. The work on squashed light spectroscopy of two-level atoms was recently extended to include simultaneous squeezing and squashing [3].…”
Section: Two-level Atommentioning
confidence: 99%
“…There are various ways of achieving this including the one pictured, which is detailed in Ref. [5]. The resultant field, b(t), is incident on a two-level atom.…”
Section: B Squashed Lightmentioning
confidence: 99%
See 3 more Smart Citations